2011
DOI: 10.1007/s11214-011-9804-x
|View full text |Cite
|
Sign up to set email alerts
|

Deducing Electron Properties from Hard X-ray Observations

Abstract: X-radiation from energetic electrons is the prime diagnostic of flare-accelerated electrons. The observed X-ray flux (and polarization state) is fundamentally a convolution of the cross-section for the hard X-ray emission process(es) in question with the electron distribution function, which is in turn a function of energy, direction, spatial location and time. To address the problems of particle propagation and acceleration one needs to infer as much information as possible on this electron distribution funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
171
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 155 publications
3
171
0
4
Order By: Relevance
“…Similarly, the thin-target hard X-rays are calculated as described in (e.g., Holman et al 2011;Kontar et al 2011, as the recent RHESSI reviews)…”
Section: X-ray Emissionmentioning
confidence: 99%
“…Similarly, the thin-target hard X-rays are calculated as described in (e.g., Holman et al 2011;Kontar et al 2011, as the recent RHESSI reviews)…”
Section: X-ray Emissionmentioning
confidence: 99%
“…2002 July 23 flare, demonstrated that the actual spectrum does contain deviations from a simple power-law (Piana et al 2003;Kontar et al 2011a), we assume a single power-law in the electron spectrum for the purposes of our analysis. For each flare, the looptop source was fitted with a thin-target model and the footpoint sources were fitted using a thick-target model (see Kontar et al 2011a, for details). Assuming looptop source is a thin-target emission, the photon flux detected at the Earth is the convolution of the electron distribution and the bremsstrahlung cross-section.…”
Section: Spectral Fittingmentioning
confidence: 99%
“…Dennis et al 2011;Holman et al 2011;Kontar et al 2011a, as recent reviews). These spatially resolved observations indicate appearances of distinct coronal and footpoint X-ray sources.…”
Section: Introductionmentioning
confidence: 98%
“…The "cold thick-target" model CTTM (Brown 1971;Syrovatskii & Shmeleva 1972) has proved popular because it provides a straightforward relationship between the bright X-ray emission from the chromospheric footpoints and the source coronal electron distribution. However, many RHESSI observations are not consistent with the CTTM or produce challenging results (Holman et al 2011;Kontar et al 2011), which demonstrates that essential physics is missing from the standard model.…”
Section: Introductionmentioning
confidence: 99%